A new arboreal Lepidodactylus (Reptilia: Gekkonidae) from Espiritu Santo Island, Vanuatu: from egg to holotype - Ineich, Ivan (Zootaxa, 2008)
Lepidodactylus buleli is a new gecko from Espiritu Santo Island, central Vanuatu, Melanesia. This species most closely resembles L. pulcher from Admiralty Islands (Papua New Guinea) by its elevated number of midbody scale rows, and belongs to Brown and Parker’s (1977) Group II based on having an entire terminal scansor on all digits followed by two or three divided or deeply notched subterminal scansors on digits II–V. It differs from other Group II species in having the following combination of character states: a high number of scales around midbody, relatively weak dilation of digits, slight webbing of toes III and IV, cloacal spurs, and an original coloration. This species lives in myrmecophilous plants hanging high on trees in the deep primary forest on the west dry coast of Espiritu Santo Island. It also is the first lizard known from a holotype collected as an egg in the field, hatched in captivity, and grown until reaching adult size, allowing its description.